2018
DOI: 10.1021/acs.nanolett.7b04842
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Local Molecular Tension Using Intercalated DNA Fluorescence

Abstract: The ability to measure mechanics and forces in biological nanostructures, such as DNA, proteins and cells, is of great importance as a means to analyze biomolecular systems. However, current force detection methods often require specialized instrumentation. Here, we present a novel and versatile method to quantify tension in molecular systems locally and in real time, using intercalated DNA fluorescence. This approach can report forces over a range of at least ∼0.5–65 pN with a resolution of 1–3 pN, using comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…To assess to what extent SYBR Gold or SYBR Green I binding lengthens the DNA contour, we first performed DNA stretching experiments in the presence of increasing concentrations of dye on torsionally relaxed (nicked) DNA. We focused on the force regime <5 pN for our force–extension measurements: in this regime the DNA extension is well described by the worm-like chain (WLC) model of entropic stretching elasticity ( 45 ) and we can neglect enthalpic contributions to stretching and the force-dependence of intercalative binding ( 3 , 15 , 46 ). In the absence of dye the response of DNA to force shows the characteristic response of entropic stretching elasticity (Figure 2B , dark blue circles).…”
Section: Resultsmentioning
confidence: 99%
“…To assess to what extent SYBR Gold or SYBR Green I binding lengthens the DNA contour, we first performed DNA stretching experiments in the presence of increasing concentrations of dye on torsionally relaxed (nicked) DNA. We focused on the force regime <5 pN for our force–extension measurements: in this regime the DNA extension is well described by the worm-like chain (WLC) model of entropic stretching elasticity ( 45 ) and we can neglect enthalpic contributions to stretching and the force-dependence of intercalative binding ( 3 , 15 , 46 ). In the absence of dye the response of DNA to force shows the characteristic response of entropic stretching elasticity (Figure 2B , dark blue circles).…”
Section: Resultsmentioning
confidence: 99%
“…Our in silico analysis showed that let-7 targets vinculin (VC), a protein connecting integrins to actin filaments, and that is recruited to focal adhesions (FAs) in response to force. VCL is suggested to be linked to FA mechanosensitivity and it is essential for FA stabilization under force (King et al, 2018). Migration of satellite cells (SC), necessary for skeletal muscle development and regeneration, is strictly dependant on the formation of mature FA connecting the cell to the extracellular matrix (Goetsch et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Condensation commenced at the free-end of the molecule, where a compact structure initially formed and then gradually increased in intensity as it moved towards the anchor point ( Figure 1C). It is important to note that the hydrodynamic flow stretches DNA molecules with a line-tension that decreases from a maximum value at the molecule's attachment point to zero at the free end 36,37 . Hence, while our TIRF results clearly demonstrate DNA condensation by PARP1 is initiated at the free end, it is not possible to distinguish whether this is caused by the presence of a double-strand break or the lower tension towards the end.…”
Section: Fluorescence Microscopy Demonstrates Condensation Of Dna By mentioning
confidence: 99%